CHEMICAL BOND OF IONIC AND PARTIALLY COVALENT CRYSTALS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
Rock Salt, sodium chloride is an ionic crystal and is the example of face centered cubic (fcc) lattice. The basis consists of one Na atom and one Cl atom separated by one-half the body diagonal of a unit cube.In sodiumchloride, sodium atom loses its outer electron and so acquires an excess of positive charge while the Cl atom has acquired the electron lost by the Na atom into its structure completing the M electron group and at the same time acquiring an excess of negative charge. Two such ions will attract one another because of the electrostatic forces between their excess charges .But they can not approach to within less than a certain distance owing to strong forces of repulsion which must set in when their outer electron shells come in to close proximity.When the centers of the two ions come within a certain distance of one another, attraction and repulsion balances and they can approach no closer and it is in this sense we must think of them as possessing a definite radius.